Italian banking supervision under the SSM principles: An analysis of the sanctioning activity - Chiara Guerello; Pina Murè; Marco Spallone (LUISS Guido Carli, Department of Economics and Finance, Arcelli Centre for Monetary and Financial Studies, 2017)
This investigation exploits a newly built database, which merges the balance sheets data of Italian banks with data on the civil penalties inflicted by the main Italian Supervisory Authorities (i.e. Bank of Italy and Consob) in the last decade. This investigation evaluates the effect of the banking supervision in Italy by analyzing the banks performances before and after enforcement actions. The scope of the analysis is twofold: we identify the main determinants of the probability of civil penalty and we evaluate the effects of these enforcement actions on banks performance. The results underline the predictive role played by efficiency, productivity, transparency, and riskiness, mainly funding and interest risk, as well as, by the business orientation. Moreover, a positive causality has been detected between the sanction event and the banks performance, but only to the extent for which the penalty induces a change in the banks behavior.
Keywords: G21; G28; G29; 330; Administrative Sanctions; Enforcement Actions; Bank Supervision; Bank Performance; Risk Profile